Induction Heating Process Design Using COMSOL® Multiphysics Software - Didi Istardi; Andy Triwinarko (Universitas Ahmad Dahlan, 2011)
Induction heating is clean environmental heating process due to a non-contact heating process. There is lots of the induction heating type that be used in the home appliance but it is still new technology in Indonesia. The main interesting area of the induction heating design is the efficiency of the usage of energy and choice of the plate material. COMSOL® Multiphysics Software can be used to simulate and estimate the induction heating process. Therefore, the software can be used to design the induction heating process that will have a optimum efficiency. The properties of the induction heating design were also simulated and analyzed such as effect of inductor’s width, inductor’s distance, and conductive plate material. The result was shown that the good design of induction heating must have a short width and distance inductor and used silicon carbide as material plate with high frequency controller.